Menumbuhkembangkan Literasi Finansial Siswa Sekolah Dasar - Krisdayanthi, Astrid; Wijaya, I Komang Wisnu Budi (Universitas Nusantara PGRI Kediri, 2023)
Financial literacy is important to master in the information and free market era. Therefore, financial literacy is included in the literacy competencies programmed in the National Literacy Movement (Gerakan Literasi Nasional). In fact, the Indonesian nation's financial literacy is still not satisfactory. Thus it is important to instill financial literacy in children from elementary school age. This study aims to analyze strategies for developing financial literacy in elementary school-aged children. This research is classified as library research. This data source comes from various literatures on elementary school children and financial literacy. Data were analyzed descriptively using content analysis techniques. The results of the study show that financial literacy can be developed in elementary school-aged children in a contextual way that involves parents and teachers.